2018
DOI: 10.2196/11147
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking App Use Among Primary Health Care Professionals: Web-Based Cross-Sectional Survey

Abstract: BackgroundSeveral studies have been conducted to analyze the role social networks play in communication between patients and health professionals. However, there is a shortage of studies in relation to communication among primary health professionals, in a professional context, using the various mobile phone apps available.ObjectiveThe objective of our study was to explore mobile phone social networking app use among primary health care professionals for work-related purposes, by comparing the most widely used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
2
21
0
1
Order By: Relevance
“…In our study, the rate of social network users was high but consistent with data from previous studies that reported rates ranging from 50% to 88% among health care professionals [ 17 - 19 ]. The rate of WhatsApp users was also similar to that in a recent report, in which it was found that 98% of primary health care professionals used WhatsApp [ 17 ]. Social networks are known to be involved in the dissemination of “fake news” and rumors [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the rate of social network users was high but consistent with data from previous studies that reported rates ranging from 50% to 88% among health care professionals [ 17 - 19 ]. The rate of WhatsApp users was also similar to that in a recent report, in which it was found that 98% of primary health care professionals used WhatsApp [ 17 ]. Social networks are known to be involved in the dissemination of “fake news” and rumors [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, people who responded to the Google survey may be more familiar with the use of social networks than other health care workers. However, the use of conventional email diffusion allowed us to constitute a control group with a significant number of respondents and a rate of social network users that is comparable to those described among health professionals [ 17 - 19 ]. Third, we estimated anxiety with a single question on a Likert scale without considering multiple psychological components (depression, anxiety, insomnia, and distress) and without using a specific neuropsychological test as previously described [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the rate of social network users was high but consistent with data from previous studies that reported rates ranging from 50% to 88% among health care professionals [17][18][19]. The rate of WhatsApp users was also similar to that in a recent report, in which it was found that 98% of primary health care professionals used WhatsApp [17].…”
Section: Comparison With Prior Worksupporting
confidence: 91%
“…Their impact on improving efficiency within health care organizations by promoting better time management and improved communications with other health care colleagues over the internet, means they are increasingly used in day-to-day clinical work. 10,11…”
Section: Introductionmentioning
confidence: 99%